Antigen presentation between T cells drives Th17 polarization under conditions of limiting antigen - Boccasavia, Viola L. (Cell Rep, 2021)
T cells form immunological synapses with professional antigen-presenting cells (APCs) resulting in T cell activation and the acquisition of peptide antigen-MHC (pMHC) complexes from the plasma membrane of the APC. They thus become APCs themselves. We investigate the functional outcome of T-T cell antigen presentation by CD4 T cells and find that the antigen-presenting T cells (Tpres) predominantly differentiate into regulatory T cells (Treg), whereas T cells that have been stimulated by Tpres cells predominantly differentiate into Th17 pro-inflammatory cells. Using mice deficient in pMHC uptake by T cells, we show that T-T antigen presentation is important for the development of experimental autoimmune encephalitis and Th17 cell differentiation in vivo. By varying the professional APC:T cell ratio, we can modulate Treg versus Th17 differentiation in vitro and in vivo, suggesting that T-T antigen presentation underlies proinflammatory responses in conditions of antigen scarcity.